2014
DOI: 10.1038/ejhg.2014.150
|View full text |Cite
|
Sign up to set email alerts
|

De novo missense mutations in the NAA10 gene cause severe non-syndromic developmental delay in males and females

Abstract: Recent studies revealed the power of whole-exome sequencing to identify mutations in sporadic cases with non-syndromic intellectual disability. We now identified de novo missense variants in NAA10 in two unrelated individuals, a boy and a girl, with severe global developmental delay but without any major dysmorphism by trio whole-exome sequencing. Both de novo variants were predicted to be deleterious, and we excluded other variants in this gene. This X-linked gene encodes N-alpha-acetyltransferase 10, the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(151 citation statements)
references
References 52 publications
5
145
0
1
Order By: Relevance
“…Another exome sequence study identified a NAA10 missense mutation, p. R116W (exon 5), in an intellectual disability syndrome [125]. Yet, another de novo missense variant in the NAA10 gene, p. V107F (exon 6), was identified in an unrelated girl with severe global development delay [20]. Based on 3D homology modeling it was suggested that Naa10 R116W has impaired catalytic activity, due to interference with CoA binding.…”
Section: Human Disorders Caused By Nat Mutationsmentioning
confidence: 97%
“…Another exome sequence study identified a NAA10 missense mutation, p. R116W (exon 5), in an intellectual disability syndrome [125]. Yet, another de novo missense variant in the NAA10 gene, p. V107F (exon 6), was identified in an unrelated girl with severe global development delay [20]. Based on 3D homology modeling it was suggested that Naa10 R116W has impaired catalytic activity, due to interference with CoA binding.…”
Section: Human Disorders Caused By Nat Mutationsmentioning
confidence: 97%
“…Another group used exome sequencing to identify a R116W mutation in a boy and a V107F mutation in a girl in two unrelated families with sporadic cases of non-syndromic intellectual disabilities, postnatal growth failure and skeletal anomalies (Rauch et al, 2012; Popp et al, 2014). A relatively mild phenotype in the boy compared to a strong defect in the girl correlates with the remaining catalytic activity of Naa10 as measured in in vitro NTA assays, suggesting that the “N-terminal acetyltransferase deficiency is clinically heterogeneous with the overall catalytic activity determining the phenotypic severity” (Popp et al, 2014).…”
Section: Mammalsmentioning
confidence: 99%
“…A relatively mild phenotype in the boy compared to a strong defect in the girl correlates with the remaining catalytic activity of Naa10 as measured in in vitro NTA assays, suggesting that the “N-terminal acetyltransferase deficiency is clinically heterogeneous with the overall catalytic activity determining the phenotypic severity” (Popp et al, 2014). In a study from 2013 where 106 genes proposed to be involved in monogenic forms of X-linked intellectual disability (XLID) were reassessed using data from the National Heart, Lung, and Blood (NHLBI) Exome Sequencing Project, this mutation in Naa10 reported in 2012 was marked as “awaiting replication” with at least one other family (Piton et al, 2013).…”
Section: Mammalsmentioning
confidence: 99%
“…About 50%-70% of proteins are N-terminally acetylated in yeast, and 80%-90% of the soluble proteins are N-terminally acetylated in human cells (Arnesen et al 2009;Van Damme et al 2011). Mutations in NATs are associated with various phenotypes in different organisms, including in humans, where mutations in NAA10, the catalytic subunit of NatA, lead to a global developmental delay and Ogden and Lenz microphthalmia syndromes (Rope et al 2011;Esmailpour et al 2014;Myklebust et al 2015;Popp et al 2015). Despite its abundance, the molecular functions of this modification have been characterized for only a handful of cases, where N-terminal acetylation can affect protein targeting to membranes, protein-protein interactions, protein folding, or protein degradation (Urbancikova and Hitchcock-DeGregori 1994;Setty et al 2004;Arnesen et al 2010;Hwang et al 2010;Scott et al 2011;Holmes et al 2014).…”
mentioning
confidence: 99%